Stimulating PV cells at nonsilencing levels during entire stimulus presentation or late phase V1 activity impairs discrimination performance, whereas stimulating during early phase V1 activity improves performance. - Lilia Kukovska (22683586) (2025)
A) Example of grating stimuli separated by 90° for easy task (top), schematic of optogenetic manipulations activating only PV cells expressing ChR2 (middle), optogenetic stimulation timings for all four conditions aligned to stimulus onset (STIM ON) or offset (STIM OFF) (bottom). B) Normalized average discrimination performance, d’, C) normalized average probability of correct ‘go’ trials (hit rate), and D) normalized average probability of incorrect ‘no-go’ trials (false alarm rate), as a function of laser power for ‘entire’ window (black, N = 10 mice, 41 sessions) and ‘early’ window (red, N = 10 mice, 37 sessions) conditions. Data is normalized by subtracting the value of the 0 power level (see Methods). E–G) same as in B–D) but for ‘late1’ window (blue, N = 10 mice, 40 sessions) and ‘late2’ window (green, N = 8 mice, 32 sessions) conditions. All plots: shaded line is the 95th percentile of data shuffled 1,000 times, using bootstrapping with replacement. Horizontal bars with corresponding colors indicate significant deviation (p < 0.05) from no laser stimulation control condition. See also S5 Fig.